Analysis of spectrum pricing for commercial mobile services: A cross country study. (October 2021) - Sridhar, V.; Prasad, Rohit
Abstract: The Simultaneous Multiple Round Ascending Auction (SMRA) pioneered by Milgrom, Wilson and McAfee in 1994 has become a defacto standard auction mechanism for the award of radio spectrum for commercial mobile services around the world. The winning bid price in such SMRA spectrum auctions is of interest as it determines the valuation of the scarce resource by the mobile operators, and also indicates the revenue accrued to the governments as auction proceeds. We examine, using a cross-country panel dataset, the determinants of spectrum prices, of all the SMRA auctions held in about 25 countries during 1994–2019. Our findings indicate that reserve prices fixed by the auctioneer as the starting price of auctions and the competition in the auction are the two variables that significantly affect the winning bid prices positively in SMRA auctions. The effect of reserve prices is more pronounced in regional auctions held in countries such as the U.S. and India. Further, the larger the amount of spectrum put on auction, lesser is the winning bid price, thereby indicating the traditional supply-demand relationship. Based on these findings, we provide policy prescriptions on fixing appropriate reserve prices, providing a clear visibility of spectrum availability, and increasing competition in mobile services for effective use of scarce radio spectrum. Highlights: The winning bid prices are of interest in the auctioning of radio spectrum for mobile services. Analyze various factors that affect wining spectrum prices of all SMRA auctions held worldwide during 1994–2019 . Use of pooled OLS and fixed-effect models for empirical analysis Reserve prices and competition in auctions positively affect winning spectrum prices. The amount of spectrum put on auction negatively affects winning bid prices.